Cysticerci seroprevalence and risk factors for neurocysticercosis: an observational hospital based study - Barakoti, M P; Rijal, S; Shyangwa, P M (Journal of Chitwan Medical College, 2015)
The serological test, enzyme linked immunosorbent assay for circulating antigen of Taenia Solium (Ag-ELISA) , was carried out in a series of 90 cases of seizure disorders, aged more than 14 years, presented to B. P. Koirala Institute of Health Sciences, Dharan, Nepal between March 2008 to May 2009. Taenia Solium antigen were detected in 13 (15%) of the patients. The diagnosis of neurocysticercosis was made in 35% cases (26 out of 75) based on clinical and neuroimaging findings. Neuroimaging was not done in 15 cases. Seropositivity was associated with neuroimaging studies consistent with NCC (OR=13.295% CI 1.43- 305.79, P= 0.014). It is significant for multiple ring enhancing lesions (P= 0.00935 for CT Head and 0.00274 for MRI Head) and not found to be statistically significant for single ring enhancing lesion (P= 0.637 for CT Head and 1.00 for MRI Head). Living in kachha house, family members >5 and age > 60 years have higher odds ratio for positive serology of cysticercosis although there was no statistical significance. The serology for cysticercosis had sensitivity of 41.5% and specificity of 98.4%.DOI: http://dx.doi.org/10.3126/jcmc.v4i4.11957